Prelimenary Study on the Accounts of Some of the Malay-Jawi 'Aqidah Texts and Commentaries - Jusoh, Che’ Razi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2011)
The works in ‘aqidah either in Arabic or in Malay Jawi have significantly contributed to the strong and correct fundamental belief of Muslims in this part of the world. Famous works which circulated during 17th century started with al-‘Aqa’id al-Nasafi were then continued primarily by the commentaries of Umm al-Barahin and Jawharat al-Tawhid. Undoubtedly they opened a great horizon in the Malay legacy of learning tradition.